Queueing Theory and Network Applications - van Do, Tien; Takahashi, Yutaka; Yue, Wuyi; Nguyen, Viet-Ha (Advances in Intelligent Systems and Computing, 2016)
The 16 papers of this proceedings have been selected from the submissions to the 10th  International Conference on Queueing Theory and Network Applications (QTNA2015) held on 17-20 August, 2015 in Ha Noi and Ha Long, Vietnam. All contributions discuss theoretical and practical issues connected with queueing theory and its applications in networks and other related fields. The book brings together researchers, scientists and practitioners from the world and offers an open forum to share the latest important research accomplishments and challenging problems in the area of queueing theory and network applications.